Percutaneous irreversible electroporation for the treatment of small renal masses: The first Canadian case series - Liu, Bonnie; Clark, Jordyn; Domes, Trustin; Wall, Chris; Jana, Kunal (Canadian Urological Association Journal, 2018)
Introduction: Irreversible electroporation (IRE) is a novel technology used in the minimally invasive treatment of small solid organ tumors. Currently, there is a paucity of literature studying treatment of small renal masses (SRMs) with IRE. Our pilot study is the first case series in Canada to use IRE in the treatment of SRMs. Methods: This retrospective cohort pilot study includes five patients (three females and two males) who presented with a SRM that was deemed not amendable to any treatment other than a radical nephrectomy or IRE. The IRE procedures were carried out by an interventional radiologist in conjunction with a urologist using the Angiodynamics NanoKnife IRE device. Results: Mean tumor size was 28 mm (range 18–39), with a mean R.E.N.A.L. nephrometry score of 8.4±0.55. Over a mean followup of 22.8 months (range 14–31), four out of the five patients did not have a radiological recurrence. No adverse events were reported after the five IRE procedures. Renal function was stable post-IRE, with no to negligible decreases in estimated glomerular filtration rate detected (range +2 to -13 mL/min/1.73 m2). Conclusions: Our pilot study demonstrates that renal percutaneous IRE is safe to use in the context of challenging-to-treat SRMs. Early radiological and renal function outcomes are encouraging, but further study is required to assess oncological success. The small sample size, retrospective nature of the study, relatively short followup, and lack of routine renal biopsy to confirm malignancy are the major limitations noted.